"It's Like Two Roles We're Playing": Parent Perspectives on Navigating Self‐Directed Service Programs with Adult Children with Intellectual and/or Developmental Disabilities. Issue 4 (15th November 2018) - Brown, Melissa; Harry, Melissa; Mahoney, Kevin
Abstract: Publicly funded self‐directed budgets for purchasing community‐based long‐term services and supports for people with intellectual and/or developmental disabilities (IDD) have become a wide‐spread service model in the United States and internationally. The current study aims to understand parents' experiences in navigating self‐directed support programs with their adult child with IDD. We utilized qualitative content analysis of interviews with 26 parents of adult children with IDD enrolled in self‐directed budget programs in five U.S. states. Twenty‐four parents reported numerous programmatic barriers to person‐centered supports falling within three thematic areas: administrative issues, budgeting challenges, and inadequate supports. Parents of adult children with IDD value self‐directed supports, although programs cannot cover all possible independent living needs due to a number of factors, including unavailability of desired supports, program rules, or budget limitations. As practices vary by program, our research suggests approaches from different programs that families may find helpful.